Gentrification: prospects for urban South African society? - Gustav Visser (Acta Academica, 2003)
The objective of this paper is to highlight some of the current international trends in the study of gentrification and assess its potential as the research site in a postapartheid urban context. In the light of international experience and the changing spatialities of post-apartheid cities, it is argued that recent developments in South Africa’s city-centres present classic opportunities for gentrification processes to emerge as part of urban regeneration. This exploration assesses this claim in four sections. The first deals with issues of definition, while the second reviews the main theoretical approaches currently employed in understanding gentrification processes. The third section relates this to gentrification research undertaken in South African cities, with the concluding section considering the types of gentrification research issues we might address in the post-apartheid context.